Exploring the Novel Norovirus: A Comprehensive Study and Overview - N, Varshini; M M, Himasvi; Bhat, Ramdas; A R Shabaraya (Indian Journal of Pharmacy & Drug Studies, 2023)
Norovirus is a highly contagious virus that is the leading cause of acute gastroenteritis worldwide. It is a small, non-enveloped RNA virus that is classified as a member of the Caliciviridae family. Norovirus is spread through contaminated food or water, close contact with infected individuals, or by touching contaminated surfaces and then ingesting the virus. Symptoms of norovirus infection include nausea, vomiting, diarrhea, and abdominal cramps. The virus primarily infects the epithelial cells lining the small intestine, leading to inflammation and damage of the intestinal lining, and decreased absorption of nutrients and fluid. The inflammation and damage can lead to dehydration, especially in young children, elderly individuals, and those with weakened immune systems. Norovirus also triggers an immune response in the body, which can further contribute to inflammation and damage of the small intestine. In severe cases, the inflammation and damage can lead to a temporary decrease in the body's ability to absorb nutrients, leading to malnutrition. Prevention measures include regular handwashing, proper food preparation and storage, and disinfection of contaminated surfaces. Those who are sick with norovirus should stay home and avoid close contact with others until they have been symptom-free for at least 48 hours. Additionally, it is important to educate the public about the importance of proper hygiene and the steps they can take to prevent norovirus transmission. In conclusion, norovirus is a highly contagious virus that is a leading cause of acute gastroenteritis worldwide. The virus primarily infects the small intestine, leading to inflammation and damage, and decreased absorption of nutrients and fluid. Prevention measures include proper hygiene, food preparation and storage, and avoiding close contact with infected individuals.